A Translation Shift Analysis Of Verb Phrase In Subtitling Of The Expendables 2 Movie - Permadi, Taufik Budi; , Dra. Dwi Haryanti, M.Hum; , Siti Fatimah, S.Pd. M.Hum (2013)
This research studies the verb phrases in subtitling of The Expendables 2 movie. The objectives of the study are to identify the translation shift of verb phrase and to describe the equivalence of verb phrase found in the film entitled The Expendables 2 and its subtitling. This research is a descriptive qualitative research. The data are the verb phrases found in subtitling of The Expendables 2 movie. The data sources are English and Indonesian subtitling of the film entitled The Expendables 2. The data are analyzed by using comparing method. The result of this study shows that there are two translation shifts of verb phrase, namely structure shift and level shift. Translation shift found by the writer belongs to structure shift (84 data), there are 4 or 4,76% data of verb phrase into adjective phrase, 8 or 9,52% data of verb phrase into adverbial phrase, 7 or 8,33% data of verb phrase is not translated, and 5 or 5,95% data of verb phrase into negative-positive. Translation shift found by the writer belongs to level shift (84 data), there are 3 or 3,57% data of verb phrase into adjective, 3 or 3,57% data of verb phrase into adverb, 2 or 2,38% data of verb phrase into noun, 1 or 1,19% data of verb phrase into preposition, 1 or 1,19% data of verb phrase into pronoun, and 50 or 59,52% data of verb phrase into verb. Secondly, the equivalence of translation is divided into equivalent translation and non equivalent translation. From 84 data, there are 75 data or 89,29% belongs to equivalent translation and 9 data or 10,71% belongs to non equivalent translation. From these percentages, it can be concluded that the translation shift of verb phrase in subtitling of the film entitled The Expendables 2 is an equivalent translation.